A Bibliometric Analysis of the Implementation of Diversity, Equity, and Inclusion (DEI) in the Technology Industry - Suhara, Ade; Mayasari, Nanny; Mustapa, Hassan; Lentari Rumbiak, Grace Colombine; Soekirman , Atong (West Science Social and Humanities Studies, 2024)
This study presents a comprehensive bibliometric analysis of research on Diversity, Equity, and Inclusion (DEI) in the technology industry, focusing on thematic clusters, research trends, potential research topics, and author collaborations. The analysis reveals that diversity and inclusion are central themes, with significant attention also given to gender diversity, equality, and innovation. Recent research trends highlight emerging areas such as accessibility, disability, and artificial intelligence. Potential research topics identified include accessibility and inclusive design, intersectionality, and the role of leadership in promoting DEI. The author collaboration network shows strong intra-group collaborations but limited inter-group interactions, suggesting opportunities for broader interdisciplinary research. This analysis provides valuable insights into the current state of DEI research in the tech industry and identifies key areas for future exploration to foster more inclusive and equitable environments.